2014
DOI: 10.3324/haematol.2014.104661
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of first-line treatment for chronic lymphocytic leukemia with 17p deletion

Abstract: Although uncommon in treatment-naive patients with chronic lymphocytic leukemia, deletion 17p is a high-risk disease characteristic. We analyzed and reported outcomes for 63 patients with deletion 17p chronic lymphocytic leukemia who received first-line therapy at our institution; at time of first treatment, 81% had unmutated immunoglobulin heavy chain variable gene and 58% had complex karyotype. Forty-nine patients (76%) received first-line fludarabine, cyclophosphamide, rituximab-based therapy, 6 (11%) recei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
56
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(58 citation statements)
references
References 37 publications
0
56
0
2
Order By: Relevance
“…This therapy is thus of marginal benefit in patients with 17p deletion. At MD Anderson, a study done combining FCR with granulocyte macrophage colony-stimulating factor showed that the ORR was 100% with a significant reduction in infectious complications [Strati et al 2014]. Reduced doses of FCR, such as FCR-lite, are also available which are well tolerated in the older population [Foon et al 2009].…”
Section: Conventional Therapiesmentioning
confidence: 99%
“…This therapy is thus of marginal benefit in patients with 17p deletion. At MD Anderson, a study done combining FCR with granulocyte macrophage colony-stimulating factor showed that the ORR was 100% with a significant reduction in infectious complications [Strati et al 2014]. Reduced doses of FCR, such as FCR-lite, are also available which are well tolerated in the older population [Foon et al 2009].…”
Section: Conventional Therapiesmentioning
confidence: 99%
“…65 Patients with 17p deletions or TP53 mutations have the worst prognosis and poor survival when treated with standard therapy; however, the novel Bruton tyrosine kinase (BTK) inhibitor ibrutinib has improved outcomes in this particular group of patients. 66,67 In addition to cytogenetic alterations, discrimination of CLL patients on the degree of mutation of the immunoglobulin heavy-chain variable-region (IGHV) gene also has prognostic and therapeutic importance. A mutated IGHV in CLL has long been associated with favorable outcome and was recently shown to be a key predictor of long-term remissions with chemoimmunotherapy.…”
Section: Lymphoma and Chronic Lymphocytic Leukemiamentioning
confidence: 99%
“…Ibrutinib was administered orally at a dose of 420 mg once daily and continued until disease progression or unacceptable toxicity. Ofatumumab was administered intravenously per prescribing information (300 mg for dose 1/2000 mg for doses [2][3][4][5][6][7][8][9][10][11][12]. Patients could then continue daily ibrutinib in extension study PCYC-1103-CA until progression or intolerability.…”
Section: Study Design and Treatment Planmentioning
confidence: 99%
“…Moreover, the presence of highrisk features such as unmutated immunoglobulin heavy chain variable region (IGHV), del(17)(p13.1), or transformation to high-grade lymphoma is associated with poor outcomes. [4][5][6][7][8][9][10] Thus, new and effective regimens are needed for patients with pretreated CLL.…”
Section: Introductionmentioning
confidence: 99%